Novel cryo-balloon technology for a successful pulmonary vein isolation: acute outcome and follow-up from a large multicenter Italian clinical setting. (19th May 2022) - Fassini, GM; De Simone, A; Iacopino, S; Bianchi, S; Bencardino, G; Pecora, D; Iuliano, A; Moltrasio, M; Rossi, P; Perna, F; La Greca, C; Placentino, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Complete electrical pulmonary vein isolation (PVI) by cryo-balloon approach is a well-established ablation strategy of atrial fibrillation (AF). Recently, a new cryoablation system (POLARx) with unique features has been made available for clinical use. To date, limited data exist on acute and follow-up outcome of this system in a multicentric clinical practice. Purpose: We reported the preliminary experience of this novel technology in a multicenter Italian registry. Methods: Consecutive patients (pts) undergoing AF ablation from the CHARISMA registry at 6 Italian centres were included. Protocol-directed cryoablation was delivered for 180 sec or 240 sec according to operator's preference for isolation achieved in ≤60 sec, or 240 sec if isolation occurred >60 sec or when time to isolation (TTI) was not available. The ablation endpoint was PV isolation as assessed by entrance and exit block. Rhythm monitoring during the follow-up examinations was performed via the clinical assessment of AF recurrence, ECG and Holter monitoring, according to the clinical practice of each center. All patients were followed-up for at least 6 months after the procedure. Arrhythmia recurrences within the first 3 months (blanking period) were classified as early recurrences and were not considered procedural failures Results: Six-hundred twenty-four cryoapplications from 112 pts (439 PVs) were analyzed (n=89, 79.5% paroxysmal AF, n=23, 20.5% persistent AF, mean age 61.5±9 years, 76% male, 22% with an history of AT, mean LVEF 49±10%). PVI was achieved in all pts using only cryoablation. The mean number of freeze applications per pt was 5.6±2.1 (1.4±1.2 for LSPV, 1.5±1.1 for LIPV, 1.3±0.8 for RSPV and 1.3±0.8 for RIPV), with 318 (72.4%) PVs treated with a single cryoablation (92, 21% with 2 cryoablation; 29, 6.6% with more than 2 cryoablations). Fourty-four (39.3%) pts were treated with a single application to each of the PVs. Over a median of 296[245 to 382] days of follow-up, five (4.5%) patients experienced an early recurrence of AF/AT during the 90-day blanking period. Overall, 12 patients (10.7%) suffered an AF/AT recurrence after the 90-day blanking period (median time to recurrence 200[124 to 297] days). Specifically, 8 (7.1%) patients had AF recurrence only, 3 (2.7%) had AT recurrence only and 1 (0.9%) experienced both events. One (0.9%) patient underwent a repeated ablation procedure. The proportion of patients exhibiting AF/AT recurrences was similar between AF types (10 out 89, 11.2% for paroxysmal AF vs 2 out 23, 8.7% for persistent AF, p=1.00) with a hazard ratio of 0.9 (95%CI: 0.2 to 3.9, log-rank p=0.8894). One transient phrenic nerve palsy was observed, with full recovery in the 48‐h post procedure; no major procedure-related adverse events were reported. Conclusion: In this first multicentric experience, the novel cryo-balloon system proved to be safe and effective and resulted in a very low rate of AF/AT recurrence during follow-up.